Which is better for preventing injuries: forefoot strike or rearfoot strike running?. Issue 5 (May 2018) - Fiore, David; Lauf, Brian S.; Passalacqua, Brian; Thiele, Karen
Abstract : EVIDENCE‐BASED ANSWER : They are likely about the same. Neither form of running consistently prevents injuries (SOR: B, retrospective and survey studies).